DOSIS OF AMELIORAN PLUS AND TECHNIQUE OF CUTTING THE UMBI OF RED CHICKEN (Allium ascalonicum L.) ON GROWTH AND HARVEST RESULTS - Nurhakiki, Neng Fika; Turmuktini, Tien; Mulya, Agus Surya (Journal of Innovation and Research in Agriculture, 2024)
ABSTRACT This study aims to study the effect of Shallot Bulb Cutting Technique (Allium ascalonicum L.) and Dodis Amelioran Plus on Growth and Yield. The experiment was conducted in Rancalega Village, Sukaresmi District, Garut Regency. with a place altitude of 750 m above sea level from February 2023 – May 2023. The research design used was a factorial pattern Group Random Design (RAK) consisting of 2 factors and each factor consisting of 4 levels of treatment, the first factor is P = cutting techniques including p0 = Control, p1 = Cut 1/4 part, p2 = Cut 1/2 part, p1 = Cut 1/3 part. Factor 2 is A = amelioran dose plus including a0 = 0 tons/ha, a1 = 2 tons/ha, a2 = 4 tons/ha, a3 = 6 tons/ha repeated 2 times so that there are 32 experimental plots placed randomly. The results showed that there was an interaction between the technique of cutting onion bulbs (Allium ascalonicum L.) and The ameliorant dose of 0 tons / ha gives an optimum value of 156.79, p1 is the dose of amelioran 2 tons / ha with a weight per plant of 184.59, p2 is an ameliorant dose of 4 tons / ha with an optimum weight of 195.06 and p3 is an ameliorant dose of 6 tons / ha with a weight per plant of 215.64